Analyzing the Effectiveness of Teaching Tauhid through Audiovisual Media: A Case Study at SD Negeri 004, West Balikpapan - Salwa, Syahida; Yusuf, Iskandar (Journal of Educational Research and Practice, 2024)
The basic of this reseacrh is the use of audiovisual media on the theme of Islamic Religious Education. This research aims to analyze the effectiveness of monotheism learning using audio-visual media at SDN 004 West Balikpapan. This research is descriptive qualitative in nature. The main data source is the Islamic Religious Education teacher. Data collection techniques include observation, interviews and documentation. Based on the research results: 1. The use of audiovisual media in teaching monotheism in the teaching and learning process is considered very useful because it is of interest to students and is fun, because they do not get bored in the learning process. The use of audiovisual media in the learning process helps educators achieve good learning outcomes for students in monotheism learning. 2. Obstacles encountered by educators in using audio visuals for students at SDN 004 West Balikpapan with monotheism learning material must be designed to be as interesting as possible so that students do not get bored and fed up.